Rheological and wall-slip behaviour of composite propellant suspension containing Al-nanopowder - Lade, Rohit; Wasewar, Kailas; Sangtyani, Rekha; Kumar, Arvind; Shende, Diwakar; Peshwe, Dilip (Journal of energetic materials, 2018)
Hydroxyl terminated polybutadiene composite propellant suspension mainly containing ammonium perchlorate (70%) and aluminium nanoparticles (ANP) (0-6%) was evaluated rheologically to determine the effect of wall slip occurring due to the formation of an apparent slip layer. True rheological properties have been obtained from gap-dependent steady-shear data using Tikhonov regularization method for the composite suspension. The advantage of this method is that it converts the gap-dependent steady-shear data into true rheological properties. The two-stage method can successfully establish both the true shear stress vs. shear rate behaviour and wall-slip parameters. The errors during rheological experimentation are analysed by determining the slip velocities and slip layer thickness. Slip velocity is observed to increase linearly with shear stress. Also, the slip layer thickness decreases with the increase in ANP content in the composite suspension. The maximum slip layer thickness of 2.13 µm is obtained for composition in which ANP is absent, and the same decreased to 0.24 µm for the composition containing 6% ANP. The rheological measurements show least deviation from gap-independent values as the amount of ANP in the propellant increases. Finally, a correlation of apparent slip layer thickness with normalized filler fraction is investigated to check the effect on wall-slip behaviour.